Treatment of postmenopausal vulvovaginal atrophy with estriol: a scientific update for 2014–2018 - A. D. Makatsariya; D. V. Blinov; V. O. Bitsadze; J. Kh. Khizroeva (Акушерство, гинекология и репродукция)
Due to the increase in life expectancy, today, most women live in a state of estrogen deficiency for more than a third of their life time. According to the recent document on the stages of aging of the female reproductive system (the STRAW+10 working group), there are three main stages that include the reproductive period, the menopausal transition, and postmenopause. One of the most common manifestations of postmenopause is vulvovaginal atrophy or genitourinary syndrome, which leads to a dramatic decrease in the woman’s quality of life. Up to 45 % of postmenopausal women suffer from this disorder, and 80 % of them experience a negative impact on their quality of life. The main symptoms of vulvovaginal atrophy are dryness, itching, burning, and dyspareunia. Caution must be exercised in relation to “silent” atrophy, which is not manifested by subjective complaints of vaginal mucosa atrophy, and can only be visualized by colposcopy. According to the recommendations of the International Menopause Society (IMS), updated in 2016, therapy should be started before the atrophic changes become irreversible; the treatment should continue for a long time to maintain the achieved therapeutic effect. If no symptoms other than vulvovaginal atrophy are noted, local estrogen therapy is indicated. Estriol has advantages over other medications due to its lower affinity for estrogen receptors. In earlier studies as well as those updated here (2014–2018), estriol applied topically as a vaginal cream or vaginal suppositories, has a selective effect on the urogenital tract and practically does not interfere with the proliferation of the uterine endometrium. The confirmed efficacy and safety of estriol allow for its permanent use, beginning with the starting dose and then switching to the maintenance one.